The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1088/1126-6708/2007/09/029
|View full text |Cite
|
Sign up to set email alerts
|

The Dirichlet Casimir effect for ϕ4theory in (3 + 1) dimensions: a new renormalization approach

Abstract: We calculate the next to the leading order Casimir effect for a real scalar field, within φ 4 theory, confined between two parallel plates in three spatial dimensions with the Dirichlet boundary condition. In this paper we introduce a systematic perturbation expansion in which the counterterms automatically turn out to be consistent with the boundary conditions. This will inevitably lead to nontrivial position dependence for physical quantities, as a manifestation of the breaking of the translational invarianc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 59 publications
(54 reference statements)
7
34
1
Order By: Relevance
“…We share the point of view with some authors such as the ones in [14,18] that the analytic continuation techniques are not always completely justified physically. Moreover, like the first of the aforementioned authors, we have found counterexamples, which we point out in this paper and elsewhere [29]. The counterexamples show that it alone might not yield correct physical results, and sometimes even gives infinite results [30].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…We share the point of view with some authors such as the ones in [14,18] that the analytic continuation techniques are not always completely justified physically. Moreover, like the first of the aforementioned authors, we have found counterexamples, which we point out in this paper and elsewhere [29]. The counterexamples show that it alone might not yield correct physical results, and sometimes even gives infinite results [30].…”
Section: Introductionsupporting
confidence: 54%
“…See for example Eq. (29). What is almost invariably done is to adjust the regulators so that the singular terms exactly cancel each other, i.e.…”
Section: B the Massive Casementioning
confidence: 99%
“…We finally obtain the following general result, which is also obtained in [19,20] using analogous general arguments but a slightly different method, δ m (x, t) = −3λG(x, t; x, t).…”
Section: First Order Radiative Correction To the Kink Masssupporting
confidence: 59%
“…solitons, have important manifestations in the physical properties of the systems. In particular, an alternative renormalization program has been proposed [18] which is fully consistent with the boundary conditions and its use has led to new results for the Next to Leading Order (NLO) Casimir effect within φ 4 theory [19,20]. The main purpose of this paper is to explore another manifestation of this newly proposed renormalization program by presenting an analogous study for systems with non-trivial backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…This statement necessities using the position-dependent counter-terms instead of free counter-terms in the renormalization program. This viewpoint on renormalization program has been explained in detail in previous studies [20][21][22][23][24][25][26][27] and all their physical aspects and advantages have been discussed. The same idea in the renormalization of interacting quantum field theory in the curved space time has been extensively investigated [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%